Neural signatures of the risk for bipolar disorder: a meta-analysis of structural and functional neuroimaging studies - Cattarinussi, Giulia; Wolf, Robert Christian (Bipolar disorders, 2018)
Objective Widespread functional and structural alterations in the brain have been extensively reported in unaffected relatives (RELs) of patients with bipolar disorder (BD) who are at genetic risk for BD. A sufficiently powered meta-analysis of structural (sMRI) and functional magnetic resonance imaging (fMRI) alterations in RELs is still lacking. Methods Functional and structural magnetic resonance imaging studies investigating RELs and healthy controls (HCs) published by July 2017 were included in the meta-analyses. Study procedures were conducted in accordance with the Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines. Random-effects coordinate-based meta-analyses were performed across all the studies per imaging modality using Seed-based d Mapping (SDM). For fMRI studies, meta-analyses were calculated for each task type. For sMRI studies, regional volumetric changes-analyses were estimated using R. Finally, multimodal meta-analyses of structural and functional abnormalities were performed. Results Sixty-nine imaging studies (2195 RELs and 3169 HCs) were included in the meta-analyses. RELs showed hyperactivation in the fronto-striatal regions as well as parietal hypoactivation during cognition. Also, activation was increased in the amygdala during emotional processing and in the orbitofrontal cortex during reward, respectively. Frontal and superior temporal cortex were hypertrophic in RELs. The right inferior frontal gyrus (rIFG) showed both increased activation during cognitive tasks and greater volume in RELs. Conclusions Our findings demonstrate that increased brain volume and activation are present in RELs and may represent intermediate phenotypes for the disorder. Furthermore, some neural changes including increased rIFG volume may be associated with the resilience to BD.
Gesehen am 02.04.2019